Differences in the key parameters of the individual versus relay swimming starts - Qiu, X.; Veiga, S.; Lorenzo, A.; Kibele, A.; Navarro, E. (Sports Biomechanics, 2021)
The purpose of the present study was twofold: (i) to compare the kinematic characteristics of individual and relay swimming starts; and (ii) to relate the kinematic variables to 5 m performance for both starts. Twelve elite-level swimmers performed 2 x 25 m at maximal effort (one with an individual and one with a relay start randomly). Two-dimensional direct linear transformation algorithms were used to calculate swimmers' centre of mass (CM) kinematics during each subphase. The results indicated moderate to much faster 5 m, 10 m 15 and 15 m times (29.4, 10.7 and 6.5%) for relay than individual starts as well as the differences at specific parameters, but no differences in take-off horizontal velocity between start techniques. Large correlations to performance times were found in block time, horizontal take-off velocity, take-off velocity and entry angle (r = 0.77 to 0.83) 20 for individual start, but in changeover time, take-off height and entry distance (r = 0.69 to 0.90) for relay start. Differences on swim start regulations between individual and relay events were in line with different key parameters related to start performances in each event. This should be considered by swimmers and coaches when addressing the starting improvement.